Protein phosphorylation in Streptomyces albus - Dobrová, Z; Jiresová, M; Petrík, T; Rysavý, P; Náprstek, J; Janecek, J (FEMS microbiology letters, 1990)
The phosphorylated proteins of Streptomyces albus, radioactively labeled with [32P]orthophosphate have been analyzed by gel electrophoresis and autoradiography. More than 10 protein species were found to be phosphorylated. With [32P]ATP as substrate cell free extracts phosphorylated endogenous proteins in vitro which were predominantly phosphorylated in vivo. From cell extract which exhibited active phosphorylated in vitro, a protein kinase has been partially purified. The kinase activity was identified in fractions corresponding to a 90 kDa protein.
Keywords: Bacterial Proteins; proteinkinasy; Molecular Weight; elektroforéza v polyakrylamidovém gelu; Electrophoresis, Polyacrylamide Gel; fosforylace; Protein Kinases; Streptomyces; bakteriální proteiny; Phosphorylation; molekulová hmotnost